New Acylcarnitine Ratio as a Reliable Indicator of Long-Chain 3-Hydroxyacyl-CoA Dehydrogenase Deficiency - Galina V. Baydakova; Polina G. Tsygankova; Natalia L. Pechatnikova; Olga A. Bazhanova; Yana D. Nazarenko; Ekaterina Y. Zakharova (MDPI AG, 2023)
Long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) and mitochondrial trifunctional protein (MTP) deficiencies are rare fatal disorders of fatty acid β-oxidation with no apparent genotype-phenotype correlation. The measurement of acylcarnitines by MS/MS is a current diagnostic workup in these disorders. Nevertheless, false-positive and false-negative results have been reported, highlighting a necessity for more sensitive and specific biomarkers. This study included 54 patients with LCHAD/MTP deficiency that has been confirmed by biochemical and molecular methods. The analysis of acylcarnitines in dried blood spots was performed using ESI-MS/MS. The established "HADHA ratio" = (C16OH + C18OH + C18:1OH)/C0 was significantly elevated in all 54 affected individuals in comparison to the control group. Apart from 54 LCHAD deficiency patients, the "HADHA ratio" was calculated in 19 patients with very-long-chain acyl-CoA dehydrogenase (VLCAD) deficiency. As VLCAD-deficient patients did not show increased "HADHA ratio", the results emphasized the high specificity of this new ratio. Therefore, the "HADHA ratio" was shown to be instrumental in improving the overall performance of MS/MS-based analysis of acylcarnitine levels in the diagnostics of LCHAD/MTP deficiencies. The ratio was demonstrated to increase the sensitivity and specificity of this method and reduce the chances of false-negative results.